2017
DOI: 10.24843/eeb.2017.v06.i08.p07
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Keterlibatan Kerja Terhadap Kinerja Dengan Pemediasi Komitmen Organisasional

Abstract: This study examined the effect of job involvement on job performance and organizational commitment as mediation. This study involved 135 respondents and using saturated sample which take all employee become a respondents. Likert Scale is used as a balanced assessment questionnaires and using validity and reliability for testing questionaires. The analysis tool in the research is Structural Equation Model (SEM) which using a variance-based approach with Partial Least Square (PLS) as well as to test the mediatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1
22

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 0 publications
1
8
1
22
Order By: Relevance
“…and organizational goals and objectives will be achieved more quickly (Logahan & Aesaria, 2014). This is in line with research conducted by (Septiadi et al, 2017), (Kembau et al, 2018), and (Paryati et al, 2019) which showed that job involvement had a significant positive effect on performance. In addition (Paryati et al, 2019) in his research also suggests that high work involvement will make employee performance better in supporting their work, as well as their ability to think to understand the situation, and carry out their duties with full responsibility in accordance with operating standards and existing deadlines.…”
Section: ) Work Involvement (X) Has An Effect On Employee Performance...supporting
confidence: 81%
See 2 more Smart Citations
“…and organizational goals and objectives will be achieved more quickly (Logahan & Aesaria, 2014). This is in line with research conducted by (Septiadi et al, 2017), (Kembau et al, 2018), and (Paryati et al, 2019) which showed that job involvement had a significant positive effect on performance. In addition (Paryati et al, 2019) in his research also suggests that high work involvement will make employee performance better in supporting their work, as well as their ability to think to understand the situation, and carry out their duties with full responsibility in accordance with operating standards and existing deadlines.…”
Section: ) Work Involvement (X) Has An Effect On Employee Performance...supporting
confidence: 81%
“…In this study, the researcher used two independent variables and one intervening variable, while this article itself used one independent variable and two intervening variables, namely job satisfaction and organizational commitment. 4 (Septiadi et al, 2017) The results of this study conclude that work involvement has an influence on employee performance, either directly or indirectly through organizational commitment.…”
Section: Organizational Commitment (M2)mentioning
confidence: 69%
See 1 more Smart Citation
“…Ini bahwa berarti dengan bekerja, ia dapat mengekspresikan diri dan menganggap bahwa pekerjaan merupakan aktivitas yang menjadi pusat kehidupannya. Karyawan yang memiliki tingkat keterlibatan kerja yang tinggi sangat memihak dan benar-benar peduli dengan bidang pekerjaan yang mereka lakukan (Rizwan et al, 2018;Septiadi et al, 2017). Indikator dari keterlibatan kerja itu adalah : 1.…”
Section: -139unclassified
“…Keterlibatan kerja berpengaruh positif dan signifikan terhadap Kineja karyawan pada PT XYZ dengan nilai thitung 9,335 dan p-value 0,000 (<0,05). Temuan penelitian ini sejalan dengan hasil penelitian sebelumnya dilakukan oleh Hadi (2018), Pristiyono (2019), Septiadi et al (2017), membuktikan bahwa keterlibatan kerja berpengaruh positif dan signifikan terhadap kinerja karyawan.…”
Section: Implikasi Temuan Bagi Perusahaanunclassified